MENINGKATKAN KINERJA KARYAWAN YANG EFEKTIF MELALUI KEPEMIMPINAN TRANSFORMASIONAL DI PT. TRANSPORTASI JAKARTA - Muh. Mashuri Masyhuda; A. Fauzan Fadlan; Irwan Prayitno (Media Bina Ilmiah, 2025)
The purpose of this research is to identify and analyze the influence of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration on the improvement of employee performance at PT. Transportasi Jakarta. This research uses a qualitative literature review. Literature review involves searching and reading existing written sources to obtain a theoretical foundation for the research problem, which includes the stages of identifying the research topic and objectives, searching for relevant literature, evaluating and selecting literature, classifying and organizing literature, analyzing and synthesizing literature, compiling the literature review, and drawing conclusions and identifying research gaps. The results of the analysis show that transformational leadership, which consists of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, has a positive and significant impact on employee performance. These findings suggest that companies should focus on the importance of transformational leadership in creating a positive and productive work environment.